A Synthetic Disaccharide Derivative of Diphyllin, TAARD, Activates Human Natural Killer Cells to Secrete Interferon-Gamma via Toll-Like Receptor-Mediated NF-κB and STAT3 Signaling Pathways - Yi, Long; Chen, Luxi; Guo, Xiaofeng; Lu, Ting; Wang, Haixia; Ji, Xiaotian; Zhang, Jianying; Ren, Yulin; Pan, Pan; Kinghorn, A. Douglas; Huang, Xiaohua; Wang, Li-Shu; et al. (Frontiers in Immunology, 2018)
Natural products and their derivatives have long been used as pharmacological agents in the fight against cancer. Human natural killer (NK) cells are critical in our immune system in that they are capable of destroying tumor cells directly. However, there are few reports that elucidate the role of natural products in activating NK cells. In this study, we discovered that a synthetic disaccharide derivative of diphyllin, 4-O-{[2”,3”,4”-tri-O-acetyl-α-D-arabinopyranosyl-(1”→4’)]-2’,3’-di-O-acetyl-α-L-rhamnopyranosyl}diphyllin (TAARD), can alone stimulate interferon (IFN)- secretion in primary human NK cells and the NKL cell line. Additionally, it had an additive effect with IL-12 or IL-15 on IFN- production but little adverse effects on NK cells. Mechanistically, TAARD induced the phosphorylation of NF-B and STAT3, resulting in their binding on the IFNG promoter, which was dependent on TLR1 and TLR3 signaling, respectively. STAT3 and NF-B knockdown with lentivirus shRNA as well as the NF-B specific inhibitor, N-tosyl-L-phenylalaninechloromethyl ketone (TPCK), significantly suppressed TAARD-induced IFN- generation in primary NK cells. Blockade of TLR1 and TLR3 with neutralizing antibodies considerably decreased TAARD-induced activation of NF-B and STAT3, respectively, as well as IFN- generation in NK cells. Collectively, our data suggest that TAARD can induce NK cell IFN- production through TLR1-NF-B and TLR3-STAT3 signaling pathways, rendering its potential use as an agent for cancer prevention or treatment.